ADHERENCE TOWARDS LIFESTYLE CHANGES RECOMMENDATION AMONG TYPE 2 DIABETES PATIENTS: A QUALITATIVE STUDY. - Noraishah Mohamed Nor; Sidek, Suriati; Saad, Nurulwahida; Mohd-Shukri, Nor Azwani (International Journal of Allied Health Sciences, 2019)
Lifestyle modification is one of the components in diabetes patients’ self-care practice, yet the essential element to prolonged diabetes complications. Despite new intervention strategies, most of the diabetic patients worldwide tend to ignore this component, which includes diet and physical activity changes. Adherence to lifestyle recommendations is necessary to ensure the effectiveness of the treatment, but many patients were having a problem in starting and maintaining their changes. Hence, this study elucidates in detail diabetes patients’ facilitator and difficulties in implementing lifestyle changes. Type 2 diabetes patients, both male and female who consulted dietitian, were recruited (N=30) for this study. The semi-structured interviews were developed based on the systematic review outcomes which provide comprehensive coverage of diabetes patient’s issues in adhering lifestyle changes, includes knowledge, practice, barrier, facilitator, and motivation. Face to face interview was conducted at the selected places, and the in-depth interview session took around 30 -90 minutes to be completed. Results discovered four main themes using the content analysis technique, include; self-care practices, lifestyle changes inhibitor, preventative action, and lifestyle changes enablers. Among the barrier in implementing lifestyle changes are due to food culture, food preference or habit, food availability and accessibility, lack of support and will power whereas few facilitating factors highlighted by the patients are high self-efficacy, support and have a motivating factor. Generally, with proper knowledge and strong self-efficacy could help the patient to start, adhere and maintain the lifestyle changes.